Application of Controlled-Release Urea in Rice: Reducing Environmental Risk While Increasing Grain Yield and Improving Nitrogen Use Efficiency. Issue 9 (14th May 2016) - Guo, Chen; Li, Pengfei; Lu, Jianwei; Ren, Tao; Cong, Rihuan; Li, Xiaokun
ABSTRACT: The low use efficiency of nitrogen (N) in rice production attributes to N losses and environmental pollution. One of the ways to improve N use efficiency is by using controlled-release urea (CRU). Field experiments in consecutive three years were conducted to compare the effects of six different types of CRU fertilizers on yield and N accumulation in straw and grain of rice. The special purpose was to provide information for application of CRU in rice. For three seasons, CRU-treated plants had significantly greater grain yields than conventional urea-treated (total N as basal fertilizers, Nt ) plants. The greatest grain yields were obtained from CRU-3, CRU-4, and CRU-3 treatment in 2012, 2013, and 2014, respectively. The N accumulation in rice straws and rice grains of the CRU-treated plots was significantly greater than that of the Nt treatment. Compared with that of the Nt treatment, CRU treatments increased the N use efficiency significantly, although there were differences among the six types of CRU fertilizers. It can be inferred that CRU performed significantly better than conventional urea. Generally, CRU-3 and CRU-6 were the best CRU fertilizers used in rice production in Jianghan Plain, China.